Analytical Review of the Jurisdictions and Current Ideality of Marriage and Khul’a (divorce by returning the dower: رشتہ ازدواج وخلع کی حدوداورعصری معنویت کا تحلیلی و تحقیقی جائزہ - Siddique, Hafiz Muhammad; Iqbal, Dr. Farzan; Rajpar, Muhammad Aslam (Al Khadim Research Journal of Islamic Culture and Civilization, 2021)
The Almighty Allah created the universe to express His existence and greatness. After adorning the earth with colorful blessings, He settled it with humanity. He connected human beings in the bonds of kinship and revered them in tribes and clans for recognition. They found themselves linked in the necessities of life to each other, hence He gave them a system of rights and duties, through the Prophets and Revealed Books of divine guidance that would take them to the fulfillment of the needs of their body, as well as man would not be in a state of spiritual confusion. These matters make it clear that the humen are interconnected and there are some distances between them too. Man, in his private and personal life, is somewhat independent as well as bound by social relations. If this balance of private and social life is maintained, then the atmosphere of home and society presents a view of heaven and if the balance is disturbed, it becomes a part of hell. The study evolves the analytical perspective of Marriage and Khul’a.